The Effect of Problem-Based Learning Strategy to Studentsâ€™ Ability in Writing Argumentative Text at Muhammadiyah University of Bengkulu - Dwisnu, Erlian (RADIANT: Journal of Applied, Social, and Education Studies, 2021)
The question posted in this study was â€œDid the Problem Based â€“ Learning Strategy give effect to the studentsâ€™ ability in writing argumentative text in English Study Program of Muhammadiyah University of Bengkulu?â€. The aim of this study was to examine whether problem-based learning strategies affect students' ability to write argumentative text in English Study Program of Muhammadiyah University of Bengkulu. The methodology of this research was experimental research. With 146 students, the samples for this study consisted of two classes. Class B has 20 students and class C 20 students. The researchers took courses B and C because they had similar subject-writing skills. The researcher took class B and C because they have similar skill in writing I subject.Â  The data were obtained from the pre-test before the treatment in three meetings and post-test after the treatment by using Problem-Based Learning Strategy in experimental class. Studentsâ€™ writing product is assessed by using analytical scoring rubric. The last step was the researcher discussed and concluded the data. The result of this research showed that Problem Based â€“ Learning Strategy can improve students' writing skills. Calculated using T-test formula, it was found that t-count is higher than t-table (2.9>2.0024) and the average scoreÂ  of the two classes was increased, the experimental class got increasing as much as 38.7 points, while in control class indicate the increasing as much as 3.8 points.Â  So, it can be concluded that this strategy gave a positive effect to the studentâ€™s ability in writing argumentative text.